2007
DOI: 10.1097/01.shk.0000278497.47041.e3
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Ischemia-Reperfusion-Induced Acute Lung Injury and Oncotic Cell Death in Multiple Organs

Abstract: Most acute respiratory distress syndrome studies have been focused on the lung injury. Little is known about other organs during the development of acute respiratory distress syndrome. Herein, we investigated the injury and cell death in multiple organs after intestinal ischemia-reperfusion (IIR) in C57BL/6 mice. Terminal transferase dUTP nick end labeling staining was used as a marker of cell death. Caspase 3 and cathepsin B activation as markers of caspase-dependent and caspase-independent apoptosis, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 47 publications
6
65
0
1
Order By: Relevance
“…RL and RL+NAC groups, despite being HS-induced, did not exhibit caspase-3 expression, similarly to CG. These data corroborate Mura et al 25 findings in a model of extra pulmonary I/R injury. The authors evidenced cell death in the lung, by TUNEL, in an experimental model of MODS, but not observed an increase of cellular expression of caspase 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…RL and RL+NAC groups, despite being HS-induced, did not exhibit caspase-3 expression, similarly to CG. These data corroborate Mura et al 25 findings in a model of extra pulmonary I/R injury. The authors evidenced cell death in the lung, by TUNEL, in an experimental model of MODS, but not observed an increase of cellular expression of caspase 3.…”
Section: Discussionsupporting
confidence: 92%
“…They performed electron microscopy with showed that structural changes in lung tissue were compatible with oncotic cell death 25 .…”
Section: Discussionmentioning
confidence: 99%
“…20 After deparaffinization, dehydration, and permeabilization with 20 g/ml proteinase K in 10 mmol/L Tris/HCl (pH 7.4 to 8) for 15 minutes, tetramethylrhodamine red-labeled nucleotides were detected under a fluorescence microscope. The nuclei were counterstained with Hoechst 33258 (Pierce, Rockford, IL) at a dilution of 1:5000 for 10 minutes.…”
Section: Terminal Deoxynucleotidyl Transferasemediated Deoxyuridine Tmentioning
confidence: 99%
“…Only a limited number pharmacologic treatment options have been found that provide some benefit in I/R and ALI, most of them targeting inflammatory mediators and oxidative stress pathways (7). A key aspect of I/R injury is the increased occurrence of apoptotic cell death of intestinal and bronchial epithelial cells and of type II alveolar epithelial cells (2,(8)(9)(10)(11). Apoptosis is associated with a marked up-regulation of Fas and Fas-ligand and the activation of caspase-3 in lung epithelial cells (12,13).…”
mentioning
confidence: 99%